About Anthropological Assumptions of Transhumanism - Misztal, Dawid (Hybris, 2019)
Insofar as transhumanism can be seen as a consequence of the undermining of traditional anthropological beliefs by scientific discoveries and technological progress, the issues of philosophical anthropology should be considered as one of its central themes. In this context, I try to answer why there is a lack of more systematic and thorough presentation of said issues in transhumanist discourse.